Neutrophilic and eosinophilic dermatoses associated with hematological malignancy - Maronese, Carlo Alberto; Derlino, Federica; Moltrasio, Chiara; Cattaneo, Daniele; Iurlo, Alessandra; Marzano, Angelo Valerio (Frontiers in Medicine, 2024)
Cutaneous manifestations of hematologic malignancy represent both a clinical challenge for the treating physician and a pathophysiological model for advancing the knowledge on individual neoplasms. Indeed, a growing body of evidence supports the concept of recurrent molecular defects associating with specific clinical features, as best exemplified by VEXAS. Herein neutrophilic and eosinophilic dermatoses of potential interest for both hematologists and dermatologists will be reviewed, including subcorneal pustular dermatosis-type IgA pemphigus, neutrophilic eccrine hidradenitis, Sweet’s syndrome as well as myelodysplasia cutis and VEXAS, pyoderma gangrenosum, eosinophilic annular erythema, eosinophilic dermatosis of hematological malignancy, Wells syndrome and cutaneous involvement in hypereosinophilic syndromes. Possible management approaches are discussed for each, emphasizing scenarios that require treatment of the underlying condition to achieve remission at the skin level.